Quality and Identity in Islamic Education Branding: Exploring Quality, Culture, and Sustainability - Su’udin Aziz; Ngainun Naim; Ainun Rahmah Kartika; Wildan Miftahussurur (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Branding in Islamic secondary education is crucial for institutional legitimacy, yet existing studies often focus on marketing tactics or isolated quality indicators, overlooking the deeper mechanisms that build a credible brand. This research addresses this gap by investigating how quality management drives authentic branding in two Indonesian Islamic schools with contrasting governance models: a state-run madrasah (MAN 1 Bojonegoro) and a private pesantren-based school (MAS Abu Dzarrin). Employing a qualitative multi-case design, data were collected through 24 semi-structured interviews, 120 hours of participant observation, and document analysis. Thematic analysis, assisted by NVivo, revealed a dynamic four-stage process: participatory strategic planning sets the direction; a deeply rooted quality culture embeds plans into daily routines; stakeholder satisfaction and trust amplify reputation through advocacy; and sustainability management protects achievements during periods of Leadership and market change. The study concludes that enduring branding is not a marketing veneer, but rather the organic outcome of consistently excellent practices that are embraced by the entire school community. It offers a replicable framework for faith-based institutions to achieve long-term legitimacy and trust. Branding di pendidikan menengah Islam sangat penting untuk legitimasi kelembagaan, namun studi yang ada seringkali berfokus pada taktik pemasaran atau indikator mutu yang terisolasi, mengabaikan mekanisme yang lebih dalam yang membangun merek yang kredibel. Penelitian ini mengatasi kesenjangan tersebut dengan menyelidiki bagaimana manajemen mutu mendorong branding yang otentik di dua sekolah Islam Indonesia dengan model tata kelola yang kontras: madrasah negeri (MAN 1 Bojonegoro) dan sekolah swasta berbasis pesantren (MAS Abu Dzarrin). Dengan menggunakan desain multi-kasus kualitatif, data dikumpulkan melalui 24 wawancara semi-terstruktur, 120 jam observasi partisipan, dan analisis dokumen. Analisis tematik, yang dibantu oleh NVivo, mengungkap proses dinamis empat tahap: perencanaan strategis partisipatif menetapkan arah; budaya mutu yang tertanam kuat mengintegrasikan rencana ke dalam rutinitas sehari-hari; kepuasan dan kepercayaan pemangku kepentingan memperkuat reputasi melalui advokasi; dan manajemen keberlanjutan melindungi capaian selama terjadi perubahan kepemimpinan dan pasar. Studi ini menyimpulkan bahwa branding yang berkelanjutan bukanlah lapisan pemasaran, melainkan hasil organik dari praktik-praktik unggul yang konsisten dan dijiwai oleh seluruh komunitas sekolah. Penelitian ini menawarkan kerangka kerja yang dapat direplikasi bagi lembaga berbasis agama untuk mencapai legitimasi dan kepercayaan jangka panjang.